An ethnomathematical approach to patterns and algebra the development of K-to-12 compliant learning modules for the coastal communities in Punta Buri, Ajuy, Iloilo - Seidel, Aprilyn S (University of the Philippines Visayas, 2016)
Ethnomathematics aims to draw from the cultural experiences and practices of individual learners, the communities, and the society at large and use them as vehicles not only to make mathematics learning more meaningful but, more importantly, to provide learners with the insights of mathematical knowledge embedded in their social and cultural environment. Anchored on the theory of Social Constructivism, the CoLab (Community as Laboratory) model was employed to develop learning modules that aim to contextualize mathematical concepts and processes for learners of an island village in Ajuy, Iloilo. Community immersion produced data from the locale's funds of knowledge revealing how patterns and algebra are being used consciously and unconsciously in the daily experiences and culture of the people living in the coastal community. Relevant data that were reflexive of the community members' domestic, socio-economic, and natural settings were utilized in designing various parts of the modules. After content validation by mathematics educators and relevant members of the community, the learning modules were appropriately revised prior to presentation for use of the learners. Interviews and focus group discussions with the learners revealed that while the modules were lacking as stand-alone learning materials, learning was a much more pleasant experience because they were finally able to connect abstract concepts with real-world experiences. These findings suggest that community engagement that can provide relevant context in developing learning materials plays a critical role in the materials development process.